The phenomenology of anomalous experience : perceiving the human energy field : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Psychology, Massey University, Palmerston North, New Zealand - Cooper, Rochelle (Massey University, 2003)
The construct of an energy field or aura surrounding and/or interpenetrating the human body dates back at least five thousand years, and is a cornerstone of many ancient and contemporary healing approaches. Belief in, and reports of aura perception continue to be widespread across a large number of cultures in contemporary times. Despite increasing public interest and popular press publications, little attention has been paid to this topic within mainstream psychology. Even within anomalistic or parapsychology, most studies have been limited to investigating rates of reported belief or experience. There appear to be no studies in the literature which map the phenomenological features of this experience. A four model framework suggested by earlier researchers is used to synthesize and review both academic and non-academic literature. Explanations for aura perception from the perspectives of the Psychical Model; the Scientific Model; the Clinical Model; and the Aura Imagery Model are considered. Interpretative phenomenological analysis was used to investigate in depth reports of aura perception in twelve subjects, in order to explicate the parameters of claimants' accounts, and chart the textural aspects of their experiences. Four master themes of 'The Phenomenon', 'Perceiving', 'Sharing the Experience, and 'Making Sense of the Experience' emerged from the analysis as being core aspects of the phenomenology of aura perception. Findings are considered alongside the four-model framework in order to suggest the most profitable direction for future research on this topic. Further investigations paralleling those used in the study of synesthesia are recommended, along with examination of the possible relationship between empathic sensitivity and aura perception.